Company Performance Improvement Strategy at Pt Angkasa Pura 1 Branch of General Ahmad Yani Airport, Semarang - Dzaky Yogo Ardhianza; Susilo Toto Raharjo (Jurnal Syntax Admiration, 2023)
Business is a daily activity that produces goods or services, has the aim of creating jobs, meeting daily needs with goods and services, and improving the economy of society. Business people must implement strategic steps due to increasingly fierce business competition and the emergence of the Covid-19 pandemic resulting in paralysis of the world economy (Agung, et. all 2022). analyze whether the cost leadership strategy can improve revenue performance at PT Angkasa Pura 1 Semarang. The research used is a type of qualitative research that involves the use and collection of various materials derived from potential data collection activities, namely by interviews, observations, and collecting data as necessary from documents. Techniques used in data collection by conducting in-depth interviews with respondents. Competitive strategy and business strategy, which includes industrial organization, resource-based viewpoints, dynamic capabilities, and theory. The overall cost leadership strategy is implemented to gain competitive advantage by reducing operating costs below operating costs incurred, cost suppression will have an impact on low product selling prices, so as to attract consumers while still generating profits. This research is qualitative research by conducting in-depth interviews with resource persons both from internal and external companies, where there is limited time to meet with resource persons because the interview process is carried out during working operational hours and the many activities of resource persons